Cardiac and respiratory effects of deep regional hyperthermia using an 8 MHz radiofrequency-capacitive device on patients with cancer. (19th May 2017) - Izukura, Rieko; Imada, Hajime; Hashiguchi, Nobuko; Sawatari, Hiroyuki; Ohguri, Takayuki; Miyazono, Mami; Ohta, Shin; Takakura, Chiduko; Yamasaki, Keiko; Magota, Chie; Fujita, Kanae; Kuroda, Hiromi; et al.
Abstract: Purpose: Hyperthermia (HT), an adjuvant therapy for variable cancers, may cause physiological changes in the patients, which may lead to cardiovascular problems. Among various HT treatments, the physiological effects of deep regional HT are still unclear. We examined the physiological alterations throughout deep regional HT to improve the HT safety. Materials and methods: Thirty-one patients (age: 61 ± 12 years) with cancer received HT in the thoracic or upper abdominal regions using an 8-MHz radiofrequency-capacitive-device for 50 min. Rectal temperature ( T rec ), systolic and diastolic blood pressures (SBP and DBP), pulse rate (PR), respiratory rate (RR), percutaneous oxygen saturation (SpO2 ) and sweating volume were evaluated throughout HT. Results: At 50 min after starting HT, T rec, PR and RR were significantly increased compared with the baseline values ( T rec : 38.2 ± 1.4 vs. 36.3 ± 0.8 °C, p < 0.001, PR: 104 ± 15 vs. 85 ± 16 bpm, p < 0.05, RR: 23 ± 3 vs. 21 ± 3/min, p < 0.05). Although the average SBP and DBP were both stable during HT in a recumbent position, these values dropped significantly in a standing position (SBP: 113 ± 16 vs. 127 ± 18 mmHg, p < 0.001, DBP: 70 ± 12 vs. 75 ± 13 mmHg, p < 0.01). The total amount of sweating was 356 ± 173 g/m 2 on average. Conclusions: Deep regional HT increased the deep body temperature and resulted in an increase of sweating with peripheral vasodilatation. Consequently, a significant reduction in BP would be induced on standing after HT. Careful attention is needed for patients receiving HT, especially when standing after HT.